Chronic treatment with juçara (Euterpe edulis) fruit pulp produces antihypertensive effect and improve on baroreflex sensitivity in Spontaneous Hypertensive Rats (SHR) (Research, Society and Development, 2022)
Background: Juçara açaí is a Brazilian berry with high anthocyanidin content and high antioxidant properties. A correlation between oxidative stress, hypertension and baroreflex impairment is known, however, no previous studies investigate the effect of juçara fruit pulp on hypertension. Aim: The aim of this study was to investigate antihypertensive effect of juçara (Euterpe edulis) fruit pulp in SHR animals, its antioxidant capacity and influence on baroreflex sensitivity. Methods: Chemical profile was obtained by ESI(-)-FT-ICR-MS. For biological analysis, male SHR were separated into groups: control (S), which received water; captopril (SC), which received captopril (30 mg/kg), and juçara (SJ), which received juçara pulp (4.4mL/kg). Treatments were daily performed by gavage and remained for 8 weeks. Baroreflex evaluation was made by in bolus injection of phenylephrine and sodium nitroprusside, after the analysis the heart was frozen (-80ºC) for biomolecular evaluations (AOPP, TBARS, SOD and catalase activity and protein expression). Results: The treatments promoted decrease in arterial pressure (S: 163.3±2.2; SC: 154.0±0.6; SJ: 149.0±3.8 mmHg) and improved the baroreflex sensitivity after nitroprusside activation. In addition, it promoted a decrease in AOPP and an increase in the activity of antioxidant enzymes. However, no changes were observed in protein expression. Conclusion: It was shown that juçara can promote cardiovascular benefits and its consume should be stimulated for prevention of hypertension.